Analisis Faktor-Faktor yang Mempengaruhi Perubahan Pandangan Hukum Qaul Al-Qadim dan Qaul Al-Jadid Imam Syafi’i - Supriadi; Misbahuddin; Kurniati (QISTHOSIA : Jurnal Syariah dan Hukum, 2024)
This article examines the factor analysis of the changes in legal perspectives between qaul al-qadim and qaul al-jadid of Imam Shafi'i. The study utilizes the Library Research method. The approach adopted includes a sociological approach to Islamic law and normative theology (sharia), while data collection involves reviewing literature such as books, articles, and other sources discussing the qaul al-qadim and qaul al-jadid of Imam Shafi'i. In processing the data, the author employs deductive reasoning, starting from general propositions and concluding with specific conclusions. Furthermore, the data analysis employs qualitative descriptive analysis, focusing on dominant factors influencing the changes in qaul al-qadim and qaul al-jadid of Imam Shafi'i. The conclusion explains that throughout the dynamic evolution of Imam Shafi'i's legal thought in Iraq and Egypt, he developed concepts known as qaul al-qadim and qaul al-jadid. Factors influencing the dynamics of his legal ijtihad include numerous hadiths of the Prophet Muhammad and other strong evidence, which subsequently influenced Imam Shafi'i's legal perspectives. Thus, experiences and knowledge significantly influenced the evolution of legal perspectives, supported by other factors such as social, traditional, cultural, political, and economic influences.